2021
DOI: 10.1371/journal.pone.0253280
|View full text |Cite
|
Sign up to set email alerts
|

Tonse Pamodzi: Developing a combination strategy to support adherence to antiretroviral therapy and HIV pre-exposure prophylaxis during pregnancy and breastfeeding

Abstract: To eliminate mother-to-child transmission of HIV (EMTCT), scalable strategies to enhance antiretroviral adherence for both antiretroviral therapy (ART) and pre-exposure prophylaxis (PrEP) are needed as part of integrated HIV and maternal-child health services. We developed Tonse Pamodzi (“all of us together”), an adaptable intervention integrating biomedical and behavioral components to support HIV treatment and prevention. We describe our intervention development process, which comprised formative qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…42 There are several potential intervention implications from our study. First, interventions to address barriers to PrEP initiation (ie, providing patientcentered counseling on HIV risk perception, increasing knowledge of available HIV-prevention tools, using decision aids to facilitate communication, providing adherence support) may increase PrEP acceptability and initiation, [43][44][45][46] though to our knowledge, these interventions are in early stages of implementation and none have been evaluated for use with pregnant individuals in the United States. Second, health care professional or clinic-level interventions may also increase PrEP acceptability and subsequently affect demand.…”
Section: Discussionmentioning
confidence: 99%
“…42 There are several potential intervention implications from our study. First, interventions to address barriers to PrEP initiation (ie, providing patientcentered counseling on HIV risk perception, increasing knowledge of available HIV-prevention tools, using decision aids to facilitate communication, providing adherence support) may increase PrEP acceptability and initiation, [43][44][45][46] though to our knowledge, these interventions are in early stages of implementation and none have been evaluated for use with pregnant individuals in the United States. Second, health care professional or clinic-level interventions may also increase PrEP acceptability and subsequently affect demand.…”
Section: Discussionmentioning
confidence: 99%
“…Their results reported the 91% reduced odds of adherence to infant antiretroviral prophylaxis for HIV-positive IPV survived mothers compared to their IPV-free counterparts (Hampanda, 2016). Poor adherence to infant antiretroviral prophylaxis could lead to drug resistance, treatment failure, and HIV vertical transmission (Haas et al, 2016; Hill et al, 2021; Kirsten et al, 2011; Nachega et al, 2012). Our study identified that women who experienced IPV during pregnancy or post-partum had the higher odds of having poor adherence to HIV prophylaxis for their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected from June 2020 to June 2021 in a pilot trial of an adherence support programme for women using antiretroviral drugs (ARVs) for either HIV treatment or prevention during pregnancy and breastfeeding. The intervention and pilot study are described elsewhere [ 24 , 25 ]. The sub‐study presented here was nested within the Tonse Pamodzi 2 (TP2) PrEP trial that enrolled pregnant women at risk of HIV acquisition interested in initiating daily oral PrEP ( n = 200).…”
Section: Methodsmentioning
confidence: 99%